Language-Related White-Matter-Tract Deficits in Children with Benign Epilepsy with Centrotemporal Spikes: A Retrospective Study - Kim, Hyun Ho (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: Benign epilepsy with centrotemporal spikes (BECTS) is one of the most common pediatric epilepsies, and it generally has a good prognosis. However, recent research has indicated that the epileptic activity of BECTS can cause cognitive defects such as language, visuospatial, and auditory verbal memory deficits. This study assessed language-delivery deficits in BECTS patients using diffusion-tensor magnetic resonance imaging (DTI). METHODS: T1-weighted MRI, DTI, and language tests were conducted in 16 BECTS patients and 16 age-matched controls. DTI data were analyzed using the TRActs Constrained by Underlying Anatomy tool in FreeSurfer 5.3, and 18 major white-matter tracts were extracted, which included 4 language-related tracts: the inferior longitudinal fasciculus, superior longitudinal fasciculus-parietal terminations, superior longitudinal fasciculus-temporal terminations, and uncinate fasciculus (UNC). Language tests included the Korean version of the Receptive and Expressive Vocabulary Test, Test of Problem-Solving Abilities (TOPS), and the mean length of utterance in words. RESULTS: The BECTS group exhibited decreased mean fractional anisotropy and increased mean radial diffusivity, with significant differences in both the superior longitudinal fasciculus and the left UNC (p<0.05), which are the language-related white-matter tracts in the dual-loop model. The TOPS language test scores were significantly lower in the BECTS group than in the control group (p<0.05). CONCLUSIONS: It appears that BECTS patients can exhibit language deficits. Seizure activities of BECTS could alter DTI scalar values in the language-related white-matter tracts.